Pengaruh Daya Tarik Iklan, Kemasan Produk, dan Kesadaran Merek terhadap Minat Beli Produk Tolak Angin pada Masyarakat Desa Kesamben Kabupaten Tuban - Anisah Yulinda Salsabila; Rusdi Hidayat Nugroho (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
The purpose of this study was to determine the effect of advertising attractiveness, product packaging, and brand awareness on purchase intention simultaneously and partially. The approach taken in this research is a quantitative approach. The sampling technique used was purposive sampling technique and the data collection method used was a google form questionnaire. The measurement scale used by the researcher is the ordinal scale and in analyzing the data, the researcher uses multiple linear regression analysis with the help of the SPSS program. Respondents in this study were 100 consumers of Tolak Angin Sido Muncul products which were addressed to the Kesamben Village Community, Tuban Regency. The results of this study indicate that partially there is a significant effect of 3 independent variables, namely advertising attractiveness, product packaging, and brand awareness on buying interest. In addition, simultaneously there is a significant effect of all variables on the purchase intention of Tolak Angin Sido Muncul products in the people of Kesamben Village, Tuban Regency. Keywords: Advertising Attractiveness; Product Packaging;Brand Awareness;Buying Interest